2021
DOI: 10.3389/fphar.2021.599561
|View full text |Cite
|
Sign up to set email alerts
|

Biomodulatory Treatment Regimen, MEPED, Rescues Relapsed and Refractory Classic Hodgkin’s Disease

Abstract: Introduction: Current combined intensive chemotherapy and radiation regimens yield excellent survival rates in advanced classic Hodgkin’s lymphoma (cHL). However, acute toxicity in elderly, comorbid patients can be challenging and long-term survival in refractory patients remains poor.Patients and Methods: We report on six patients with r/r HL, three patients with long-term follow-up, three newly treated, after biomodulatory therapy. All patients received MEPED (treosulfan 250 mg p.o. daily, everolimus 15 mg p… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
39
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 11 publications
(42 citation statements)
references
References 46 publications
0
39
0
Order By: Relevance
“…Recently, anakoinosis was proposed as a successful way of modulating cancer tissue homeostasis by re-establishing a new equilibrium via "tissue editing" [50]. Pro-anakoinotic drugs act as tissue master modulators, thereby preventing tissue defenses, providing a concerted regulative activity profile of a treatment schedule's single components, and may facilitate long-term tumor control or even continuous complete remission [51][52][53][54]. Importantly, this approach showed that classic pro-apoptotic drugs are un-necessary to induce long-term tumor control or continuous complete remission [55]: anakoinosis would thus bypass the intrinsic limitation of the current pro-apoptotic therapies by aiming at bio-modulation instead of cytotoxicity, possibly avoiding CRAC as suggested by in silico modeling [56].…”
Section: Discussionmentioning
confidence: 99%
“…Recently, anakoinosis was proposed as a successful way of modulating cancer tissue homeostasis by re-establishing a new equilibrium via "tissue editing" [50]. Pro-anakoinotic drugs act as tissue master modulators, thereby preventing tissue defenses, providing a concerted regulative activity profile of a treatment schedule's single components, and may facilitate long-term tumor control or even continuous complete remission [51][52][53][54]. Importantly, this approach showed that classic pro-apoptotic drugs are un-necessary to induce long-term tumor control or continuous complete remission [55]: anakoinosis would thus bypass the intrinsic limitation of the current pro-apoptotic therapies by aiming at bio-modulation instead of cytotoxicity, possibly avoiding CRAC as suggested by in silico modeling [56].…”
Section: Discussionmentioning
confidence: 99%
“…The two-step identification of drugs for repurposing encompasses the selection of appropriate combinations of approved drugs with pro-anakoinotic activity profiles for establishing novel functional status for therapeutically 'editing' tumor tissues by induction of differentiation, transdifferentiation, or establishing immunosurveillance and tumor cell death etc. (5,11,(19)(20)(21)(22)(23). The second step is to select approved targeted therapies for enhancing the biomodulatory effects or for establishing prerequisites for the induction of continuous complete remission (4,6,10,24,25).…”
Section: Two-step Drug Repurposingmentioning
confidence: 99%
“…Clinically, tumor tissue editing can adequately design tumor tissues, a prerequisite for efficacious use of mTOR inhibitors in refractory metastatic uveal melanoma or refractory Hodgkin's disease with metronomic low-dose chemotherapy and a PPARa/g agonist (21,23). In uveal melanoma long-term disease stabilization with significant improvement of ECOG status was achieved, in refractory Hodgkin's disease even induction of complete remission, moreover continuous complete remission after discontinuation of the metronomic schedule (26).…”
Section: Kras Inhibitors and Tissue Editing With Pparg Agonistsmentioning
confidence: 99%
“…Klicken oder tippen Sie hier, um Text einzugeben. But, tumor plasticity also opens a therapeutic window by tumor tissue editing, the possibility to induce completely novel tumor phenotypes by introducing therapeutically relevant editing techniques that redirect hallmarks of cancer into biologic hallmarks attenuating tumor growth or even facilitate tumor cell death as prerequisite for continuous complete remission (cCR), also in relapsed or refractory neoplasias ( 10 , 11 ). Aims of tumor tissue editing strategies may be differentiation induction in hematologic neoplasia or solid tumors, reconstitution of immunosurveillance, control of tumor-associated inflammation, inhibition of M-CRAC etc.…”
Section: Tissue Editingmentioning
confidence: 99%